La filología - Oroz, Rodolfo (Revista Chilena de Humanidades, 2015)
Professor Oroz notes the need to differentiate between Philology and Linguistics. He quotes diverse opinions on philological works, specifying that it should deal with the critica! interpretation of t exts, which demands a previous study of the language, and particularly of certain disciplines which are proper to it, so as to reconstruct the vision of the author's world and times; from there the fact that the methods of literary investigation are based on philological methods. He acknowledges the prestige that Chile has in this field of studies, mainly due to foreigners who have settled in Chile, although we cannot as yet show much in the matter of editing critica! analyses of the works of writers ancient and modem, a task which is urgent, beginning by the updating of philological bibliographies.